PERCEPATAN EKONOMI PEDESAAN MELALUI PEMBANGUNAN PERKEBUNAN KELAPA SAWIT * - Syahza, Almasdi (Universitas Muhammdaiyah Surakarta, 2011)
This research assessed the impact of oil palm plantation development to the acceleration of economic development of community in effort to alleviate poverty in rural areas. The research was conducted through survei with descriptive method. Information obtained through the approach of Rapid Rural Appraisal (RRA). The results obtained by oil palm plantation activities in the rural areas created a figure amounting to 3.03 of multiplier effect, especially in employment and business opportunity. In year 2003, the farmerâs welfare index of rural areas amounting to 1.72. It means the growth of the farmerâs welfare increased by 172 percent. In the period of 2003-2006, farmers welfare index was 0.18 and the period of 2006- 2009 also experienced positive at 0.12. It means the welfare of farmers during this period increased by 12 percent.